Soil Development in Quaternary Glacial Deposits, Waterton Park Area, Southwestern Alberta - Karlstrom, Eric (Géographie physique et Quaternaire, 1988)
ABSTRACTPedological investigations in the Waterton Park area provide a useful means of testing subdivisions of Quaternary glacial deposits based on geomorphic relations. Soils in the region, however, including Podzols, Brunisols, Luvisols, and Chernozemics, also reflect the influence of soil forming factors other than time. Nonetheless, a chronosequence can be established by comparing time-diagnostic properties of soils on different geomorphic units in areas with similar climate, vegetation, slope and parent material. Properties thought to be most diagnostic of relative soil age include thickness and degree of clay buildup in B horizons and two soil development indices which average degree of development of a number of properties. Pédologie and geomorphic data suggest surface deposits include mountain tills of three or four separate advances and continental tills of two separate advances. Mountain tills are tentatively correlated with the Late Wisconsinan (about 18 ka BP), Late and or Early Wisconsinan (about 100 to 65 ka BP). Late lllinoian (about 200 to 132 ka BP). and Early lllinoian and/or pre-lllinoian (about 400 to 700+ ka BP), whereas continental tills are tentatively correlated with the Late Wisconsinan and Late lllinoian deposits of the U.S. Midcontinent.